2010
DOI: 10.1111/j.1461-9563.2010.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal analysis of plant pests in a greenhouse using a Bayesian approach

Abstract: 1 The present study aimed to propose a method that can improve our understanding of pest outbreaks and spatio-temporal development in greenhouse crops. 2 The experiment was carried out in a greenhouse rose crop grown under integrated pest management (IPM) for 21 months. The main pests observed were powdery mildew, two-spotted spider mites and western flower thrips. A quick visual sampling method was established to provide continuous monitoring of overall crop health. 3 A Bayesian inferential approach was then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This disposition of traps was chosen (i) accordingly to a previous study that demonstrated an important homogeneity in spatial distribution of thrips in the greenhouse (Poncet et al 2010), and (ii) because placing traps this way could provide an easiest access to the YST (and thus easiest adoption of the method by growers). Traps were replaced and the trapped thrips counted on a weekly basis.…”
Section: Thrips Monitoring Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This disposition of traps was chosen (i) accordingly to a previous study that demonstrated an important homogeneity in spatial distribution of thrips in the greenhouse (Poncet et al 2010), and (ii) because placing traps this way could provide an easiest access to the YST (and thus easiest adoption of the method by growers). Traps were replaced and the trapped thrips counted on a weekly basis.…”
Section: Thrips Monitoring Methodsmentioning
confidence: 99%
“…A previous study conducted in the greenhouse (with these three cultivars) demonstrated no cultivar type effect on thrips populations (Poncet et al 2010). For thrips control, releases were conducted of Neoseiulus (Amblyseius) cucumeris (Oudemans) and occasionally of Franklinothrips vespiformis (Crawford).…”
Section: Greenhouse and Cropping Conditionsmentioning
confidence: 96%
“…Information on the locations of temporary or recurring clusters of pests observed in the previous week or over a 3-yr period in the greenhouse (Poncet et al 2008(Poncet et al , 2010 did not help optimize sampling plans. Zones of foci infection, as identiÞed by stem observations, do not seem to remain in a Þxed position from 1 wk to the next, particularly for powdery mildew.…”
Section: Discussionmentioning
confidence: 93%
“…If there were more foci than grid points, foci were selected at random. Conversely, we also constructed grids with foci identiÞed as recurring foci over a 3-yr period in this crop (Poncet et al 2008(Poncet et al , 2010. We completed the sampling grid with a random selection of sampling units.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation